Evaluating the Relationship Between Gastrointestinal Bleeding and Valvular Heart Disease: A Systematic Review of Clinical Studies - Jacob J. Gries; Kamran Namjouyan; Hafeez Ul Hassan Virk; Mahboob Alam; Hani Jneid; Chayakrit Krittanawong (Gastrointestinal Disorders)
Background: Gastrointestinal angiodysplasia is a significant vascular anomaly characterized by dilated, tortuous blood vessels in the gastrointestinal tract. The current literature extensively documents the association between angiodysplasia and aortic stenosis, known as Heyde syndrome, characterized by the triad of aortic stenosis, GIB, and acquired von Willebrand syndrome. However, other valvular diseases, including mitral and tricuspid regurgitation, have also been implicated. This comprehensive systematic review aims to investigate the spectrum of valvular abnormalities, exploring the intricate mechanisms by which they contribute to gastrointestinal bleeding. Furthermore, it will evaluate the available surgical and nonsurgical treatment modalities, assessing their efficacy in mitigating the incidence of such bleeding. Methods: A comprehensive search of the Pubmed/MEDLINE database was conducted to identify relevant studies to retrieve relevant articles from August 2014 to August 2024. A combination of Medical Subject Heading (MeSH) terms and text words related to cardiac valvular diseases and GIB were used. MeSH terms included “gastrointestinal bleeding”, “heart valve diseases”, “hematochezia”, “heart valve prosthesis”, “bioprosthesis”, “native valve diseases”, and “mechanical valve”. Results: Forty-five papers met the inclusion criteria. Twenty-seven studies covered GIB in aortic valve disease, ten on mitral valve disease, two on tricuspid valve disease, and six on multiple valves. Conclusions: This systematic review demonstrates the association between angiodysplasia and aortic stenosis and highlights mitral regurgitation and tricuspid regurgitation as potential etiologies. Definitive management with valvuloplasty or valve replacement is vital to preventing the onset or recurrence of GIB in patients with valvular disease.